THE IMPACT OF ARTIFICIAL INTELLIGENCE ON EDUCATION OPPORTUNITIES AND CHALLENGES - Ruhshona Yuldasheva (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
Artificial Intelligence (AI) has revolutionized various sectors of society, and education is no exception. This paper explores the multifaceted impact of AI on the educational landscape, analyzing how AI technologies are enhancing teaching methods, personalizing learning experiences, and optimizing administrative tasks. While AI offers numerous opportunities, including increased accessibility and tailored education, it also presents challenges related to ethics, data privacy, and inequality. This study provides a balanced overview of the potential and pitfalls of AI in modern education and suggests pathways for effective integration.